Chlamydia pneumoniae infection of lungs and macrophages indirectly stimulates the phenotypic conversion of smooth muscle cells and mesenchymal stem cells: potential roles in vascular calcification and fibrosis. Issue 1 (10th June 2014) - Cabbage, Sarah; Ieronimakis, Nicholas; Preusch, Michael; Lee, Amy; Ricks, Jerry; Janebodin, Kajohnkiart; Hays, Aislinn; Wijelath, Errol S.; Reyes, Morayma; Campbell, Lee Ann; Rosenfeld, Michael E.
Abstract Two hallmarks of advanced atherosclerosis are calcification and fibrosis. We hypothesized that Chlamydia pneumoniae infection may contribute to atherosclerosis by inducing the conversion of vascular smooth muscle cells to calcifying cells or by converting mesenchymal stem cells to osteochondrocytic or fibroblastic phenotypes. In this study, direct infection of bovine aortic smooth muscle cells (BSMCs) did not induce the expression of alkaline phosphatase or the deposition of extracellular calcium phosphate. However, conditioned media from C. pneumoniae‐infected macrophages accelerated conversion of BSMCs to a calcifying phenotype. Treatment of the conditioned media with an anti‐TNF‐alpha blocking antibody abrogated this stimulatory effect. Treatment of perivascular Sca‐1+, CD31−, CD45− cells from apoE−/− mouse aortas with the conditioned media from infected macrophages induced the Sca‐1+ cells to produce collagen II, an additional marker of an osteochondrocytic phenotype. Treatment of mouse coronary perivascular Sca‐1+, CD31−, CD45− cells with the supernatant from homogenates of C. pneumoniae‐infected mouse lungs as compared to noninfected lungs induced expression of the Collagen 1α1 gene and deposition of collagen. Therefore, an increase in plasma cytokines or other factors in response to respiratory infection with C. pneumoniae or infection of macrophages within the blood vessel could contribute to both calcification and fibrosis of advanced atherosclerotic lesions.